基于MFC和Pro/TOOLKIT的NGW型行星减速器参数化设计 - 赵丽娟; 张双; 伍正军 (Jixie Chuandong, 2012)
In the integrated development environment of the VC,3D parametric design system of the NGW planetary reducer is developed by MFC and Pro/E secondary development kit Pro/TOOLKIT,Namely,achieved automatic update and assembly of the parts of the reducer is achieved,and the reasonableness of the design can be checked.The design process is Simplified and the design cycle is shortened.Parametric designed for other products provides valuable experience.